Crowdsourcing to support training for public health: A scoping review. - Kadija M Tahlil; Ucheoma Nwaozuru; Donaldson F Conserve; Ujunwa F Onyeama; Victor Ojo; Suzanne Day; Jason J Ong; Weiming Tang; Nora E Rosenberg; Titi Gbajabiamila; Susan Nkengasong; Chisom Obiezu-Umeh; et al. (Public Library of Science (PLoS), 2023)
Crowdsourcing is an interactive process that has a group of individuals attempt to solve all or part of a problem and then share solutions with the public. Crowdsourcing is increasingly used to enhance training through developing learning materials and promoting mentorship. This scoping review aims to assess the literature on crowdsourcing for training in public health. We searched five medical and public health research databases using terms related to crowdsourcing and training. For this review, the concept of crowdsourcing included open calls, designathons, and other activities. We used a PRISMA checklist for scoping reviews. Each full-text was assessed by two independent reviewers. We identified 4,071 citations, and 74 studies were included in the scoping review. This included one study in a low-income country, 15 studies in middle-income countries, 35 studies in high-income countries, and 11 studies conducted in multiple countries of varying income levels (the country income level for 12 studies could not be ascertained). Nine studies used open calls, 35 used a hackathon, designathon or other "a-thon" event, and 30 used other crowdsourcing methods, such as citizen science programs and online creation platforms. In terms of crowdsourcing purpose, studies used crowdsourcing to educate participants (20 studies), develop learning materials (17 studies), enhance mentorship (13 studies) and identify trainees (9 studies). Fifteen studies used crowdsourcing for more than one training purpose. Thirty-four studies were done in-person, 31 were conducted virtually and nine used both meeting options for their crowdsourcing events. Seventeen studies generated open access materials. Our review found that crowdsourcing has been increasingly used to support public health training. This participatory approach can be a useful tool for training in a variety of settings and populations. Future research should investigate the impact of crowdsourcing on training outcomes.